2018
DOI: 10.1287/mnsc.2016.2703
|View full text |Cite
|
Sign up to set email alerts
|

Translated Attributes as Choice Architecture: Aligning Objectives and Choices Through Decision Signposts

Abstract: Every attribute can be expressed in multiple ways. For example, car fuel economy can be expressed as fuel efficiency (“miles per gallon”), fuel cost in dollars, or tons of greenhouse gases emitted. Each expression, or “translation,” highlights a different aspect of the same attribute. We describe a new mechanism whereby translated attributes can serve as decision “signposts” because they (1) activate otherwise dormant objectives, such as proenvironmental values and goals, and (2) direct the person toward the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 40 publications
4
62
1
Order By: Relevance
“…The findings suggest that tailoring the scale of energy labels based on the expected lifetime of a given product or providing multiple translations of energy-efficiency metrics could help guide decisions (Camilleri and Larrick 2014;Ungemach et al forthcoming). To some extent, this is already happening: the US Environmental Protection Agency recently redesigned new vehicle labels to include gallons per miles, multiple cost estimates, comparisons with other vehicles in the same class, and environmental ratings (US Environmental Protection Agency 2015).…”
Section: Do Other Cognitive Limitations Inhibitmentioning
confidence: 99%
“…The findings suggest that tailoring the scale of energy labels based on the expected lifetime of a given product or providing multiple translations of energy-efficiency metrics could help guide decisions (Camilleri and Larrick 2014;Ungemach et al forthcoming). To some extent, this is already happening: the US Environmental Protection Agency recently redesigned new vehicle labels to include gallons per miles, multiple cost estimates, comparisons with other vehicles in the same class, and environmental ratings (US Environmental Protection Agency 2015).…”
Section: Do Other Cognitive Limitations Inhibitmentioning
confidence: 99%
“…Choice architecture can be thought of as lying along a continuum anchored at one end by "nudges" and at the other end by "signposts" (Soll, Milkman, & Payne, 2014;Ungemach, Camilleri, Johnson, Larrick, & Weber, 2018). The distinction between nudges and signposts maps closely to the distinction some researchers have recently made between "nudges" and "boosts" (Grüne-Yanoff & Hertwig, 2016;Hertwig, 2017;Hertwig & Grüne-Yanoff, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…First, research on different types of energy saving behaviors provides conflicting evidence on whether jointly presenting environmental and financial messaging increases energy saving likelihood. One empirical study on motivating participation in an energy conservation program found no difference between financial messaging alone and financial plus environmental messaging [20], while another study of vehicle purchases found that adding environmental benefits in addition to financial benefits increased likelihood of selecting a more energy efficient vehicle [11]. As noted in section 1.1, the experimental study on large efficiency investments found no statistically significant effect of presenting environmental benefits alone [21].…”
Section: Environmental Versus Financial Motivationsmentioning
confidence: 98%
“…Second, studies comparing the effect of financial and environmental motivations on investments in energy efficiency measures have found that political ideology [20,22] and/or environmental values [11] moderate the effect of environmental messaging. Thus far, results differ on whether environmental messaging reduces or has no effect on likelihood to engage in energy saving behavior for those with a conservative political ideology.…”
Section: Environmental Versus Financial Motivationsmentioning
confidence: 99%
See 1 more Smart Citation